2005
DOI: 10.1007/s00134-005-2757-3
|View full text |Cite
|
Sign up to set email alerts
|

Studying outcomes of intensive care unit survivors: the role of the cohort study

Abstract: The online version of the original article can be found at http:// dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The study of Livingston et al 16 demonstrated that less than half of the patients who underwent trauma returned to work and more than two-thirds reported a lower level of activity than before the trauma after follow-up of 3 years. Longer-term follow-up will improve our understanding of the nature and duration of ICUacquired deficits 17 and what length of time is sufficient to accurately determine outcome. Furthermore, to our knowledge, which patient characteristics (such as age and sex) and surgical classifications are related to long-term HRQOL have yet to be addressed.…”
Section: Cme Available Online At Wwwjamaarchivescmecom and Questionmentioning
confidence: 99%
“…The study of Livingston et al 16 demonstrated that less than half of the patients who underwent trauma returned to work and more than two-thirds reported a lower level of activity than before the trauma after follow-up of 3 years. Longer-term follow-up will improve our understanding of the nature and duration of ICUacquired deficits 17 and what length of time is sufficient to accurately determine outcome. Furthermore, to our knowledge, which patient characteristics (such as age and sex) and surgical classifications are related to long-term HRQOL have yet to be addressed.…”
Section: Cme Available Online At Wwwjamaarchivescmecom and Questionmentioning
confidence: 99%
“…The SF-36, which measures health status, is often used as an indicator of HRQOL (Dowdy et al 2005) and was used in this study. Eight subscales are included in the scale, Physical functioning (10 items), Role physical (four items), Bodily pain (two items), General health (five items), Mental health (five items), Role emotional (three items), Social functioning (two items) and Vitality (four items) (Ware et al 1993).…”
Section: Data Collectionmentioning
confidence: 99%
“…With the availability of interventions to decrease mortality in the ICU, there is a growing interest in the longterm outcomes of critically ill patients. [125][126][127] These include late mortality, physical morbidity, cognitive dysfunction, psychiatric disorders, poor functional status, and decreased quality of life. 125,126 It has become apparent that many of these complications are linked, and the study of post-ICU outcomes must carefully account for possible confounding factors.…”
Section: Long-term Cognitive Impairmentmentioning
confidence: 99%